Urgensi Sosialisasi Koperasi Syariah Dalam Upaya Peningkatan Pemahaman Masyarakat Menggunakan Koperasi Syariah : (Study Kasus Kota Tanjungbalai) - Raja Putri Salsabila; Azhari Akmal Tarigan (Student Research Journal, 2023)
This research aims to determine the role of socialization carried out by the Islamic economics student internship group at the North Sumatra State Islamic University in an effort to increase public understanding of Sharia Cooperatives. This research is a descriptive analysis research with a qualitative approach. The data collection techniques used were observation, interviews and documentation. Data analysis in qualitative research is an effort carried out by working on data, grouping data, selecting it into manageable units, looking for and finding patterns, determining what is important and what is to be studied, and concluding nothing that can be told to other people. The results of the research show that the socialization role carried out by the Islamic Economics Student Internship Group at North Sumatra State Islamic University plays a very important role in cooperative business activities as well as in increasing public understanding regarding Sharia Cooperatives, accompanied by excellent strategies to attract public interest.